Indigenous Economies, Theories of Subsistence, and Women: Exploring the Social Economy Model for Indigenous Governance - Kuokkanen, Rauna (American Indian Quarterly, 2011)
This article considers the significance of indigenous economic systems in contemporary society. It argues that indigenous economic systems have to be taken into account much more systematically than thus far in considerations of indigenous governance. The article contends that indigenous economic systems need to play a more central role in envisioning and shaping meaningful, comprehensive, and sustainable systems of contemporary indigenous self-governance. If indigenous economies are not taken into account, there is a serious danger of losing the very identities that constitute indigenous peoples. ...The article consists of three sections. The first section discusses definitions and contemporary significance of subsistence and indigenous economies. It questions the prevailing narrow, economistic analyses and interpretations of subsistence. Although economic development projects such as resource extraction may improve fiscal independence and strengthen the economic base of indigenous communities, they also present serious threats to indigenous economies.The second section examines the relationship between subsistence and wage labor, particularly from the perspective of women. It also considers the “war on subsistence” waged by the development and modernization theories, which continue to contribute to views of subsistence as “primitive” and “pre-modern.” The third section takes a closer look at the often glossed over roles of indigenous women in subsistence activities. It questions the conventional binary economic roles of man-the-hunter versus woman-the-gatherer and argues for a broader lens when assessing economic roles and divisions of labor along gendered lines. The article concludes with an examination of indigenous economic systems and the concept of the social economy as a foundation for contemporary indigenous governance. --From Introduction